Alternatif Sistem Penataan Infrastruktur Kawasan Permukiman Kumuh Di Kota Palangka Raya - Muhing L. Agau; Rusdi H.A.; Candra Yuliana (Media Ilmiah Teknik Sipil, 2019)
Environment Structuring is an important factor in settlement improvement efforts. As an indicator of clean and healthy neighborhoods that continuing environmental improvement quality can be measured by the presence or not, and good or poor infrastructure such as residential areas. The settlement Palangka Permai is located between the street G. Obos and Yos Sudarso Palangka Raya. It indicates that there are some drawbacks in terms of infrastructure feasibility aspects. Problems and objectives set out in this study are to determine the condition, causes and alternative systems of infrastructure arrangement residential area which is managed by the developer in the Palangkaraya city, as a basis for making alternative arrangement of the infrastructure systems to prevent neighborhoods from becoming a slum in Palangkaraya city. The results calculated scores to gauge the feasibility of infrastructure categories shows that the environmental aspect and location aspects of ordinary uncategorized. Aspects of road infrastructure, water and drainage, social facilities, buildings and technical of liquid and solid waste disposal have deserved fewer categories. The alternative system proposed settlement infrastructure is on Road infrastructure by optimizing the way the existing environment, create a new road axis, providing an environment of interconnected roads, procurement of drainage on either side of the road with a width and height of > 10% from width of pavement, optimizing the public open space, private open space, trees, and green layout, landscape and green belt areas as social facilities, oversight, and action on changes in appearance of buildings, by evaluating the ownership of the IMB and to make special rules to regulate of the building function, waste solid management (waste) needs to form an organization for the handling of waste. For the liquid wastes, handling is the local provider is to disposal wastewater system (on-site system) with system or septic tank and cubluk disposal centralized (off-site system) to create a closed channel to a combination of wastewater and surface water